Jawaban:
[tex]1. {f}^{1} (x) = 2 \times 4 \times {x}^{2 - 1} + 1 \times 11 \times {x}^{1 - 1} \\ = 8x + 11 \\ =8 \times ( - 3) + 11 \\ = ( - 24) + 11 \\ = - 13[/tex]
[tex]2. {f}^{1} (x) = 2 \times 6 \times {x}^{2 - 1} - 1 \times 4 \times {x}^{1 - 1} \\ = 12x - 4 \\ = 12 \times ( - 2) - 4 \\ = ( - 24) - 4 \\ = - 28[/tex]
[tex]3. {f}^{1} (x) = 2 \times \frac{7}{8} \times {x}^{2 - 1} + 1 \times 8 \times {x}^{1 - 1} \\ = \frac{7}{4} x + 8 \\ = \frac{7}{4} 6 + 8 \\ = \frac{42}{4} + \frac{32}{4} \\ = \frac{74}{4} \\ = 18 \frac{1}{2} [/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Jawaban:
[tex]1. {f}^{1} (x) = 2 \times 4 \times {x}^{2 - 1} + 1 \times 11 \times {x}^{1 - 1} \\ = 8x + 11 \\ =8 \times ( - 3) + 11 \\ = ( - 24) + 11 \\ = - 13[/tex]
[tex]2. {f}^{1} (x) = 2 \times 6 \times {x}^{2 - 1} - 1 \times 4 \times {x}^{1 - 1} \\ = 12x - 4 \\ = 12 \times ( - 2) - 4 \\ = ( - 24) - 4 \\ = - 28[/tex]
[tex]3. {f}^{1} (x) = 2 \times \frac{7}{8} \times {x}^{2 - 1} + 1 \times 8 \times {x}^{1 - 1} \\ = \frac{7}{4} x + 8 \\ = \frac{7}{4} 6 + 8 \\ = \frac{42}{4} + \frac{32}{4} \\ = \frac{74}{4} \\ = 18 \frac{1}{2} [/tex]